PENGENTASAN KEMISKINAN MELALUI PENGEMBANGAN EKONOMI KREATIF PERDESAAN BERBASIS POTENSI LOKAL DI KABUPATEN SUMEDANG (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2018)
Creative economy is expected to create a more sustainable economic growth compared with the industrial economy that is dependent on the resource. If the creative economy can be explored and developed based on local potentials in each region, rural development can be improved and can be a support for the people's lives, which ultimately can alleviate poverty. The research technique was conducted through descriptive survey approach, and the research place was chosen Sub-district Surian Sumedang Regency.Respondents were drawn randomly, 50 farmers. Secondary data is collected from: documents in related institutions and journals. The data and information obtained were analyzed descriptively and cross tabulation.The result of the research shows that the development of creative economy in Surian Sub-district of Sumedang Regency is faced with problems, namely: 1) the community has not been able to manage the resources possessed by the lack of knowledge and skills, 2) the lack of supporting infrastructure, and 3) the inconsistency of community development From the government, so the potential of existing resources has not been well managed. The development of creative economy based on local potential becomes very urgent to do. Development of creative economy can be done from the economic side, ie from upstream (cultivation of plants) to downstream (processing of agricultural products); Also from the cultural side (arts and ceremonies adat) and the potential of nature owned, can be used as a tourist attraction area. The local potential can be developed towards the tourism sector, by developing creative economy from upstream to downstream, cultural and nature owned, into several tour packages, such as: nature tourism, scientific tourism, cultural tourism, and culinary tourism.Keywords : creative economy, local potential, resources, rural areas, value added